Pylephlebitis Associated with Inferior Mesenteric Vein Thrombosis Treated Successfully with Anticoagulation and Antibiotics in a 37-Year-Old Male. (13th February 2020) - Abdallah, Mohamed; Gohar, Ahmad; Naryana Gowda, Smitha; Abdullah, Hafez M.; Al-hajjaj, Ali
Abstract : Pylephlebitis is a condition in which there is septic thrombophlebitis of the portal-mesenteric venous system. It is a rare condition that usually arises as a complication of an intra-abdominal infection or inflammation. Being rare, it may be overlooked as a differential in cases of abdominal pain when the more common causes have been excluded. We present a case of a 37-year-old Hispanic male who presented with acute abdominal pain and loose stools. He was initially treated for acute gastroenteritis but his clinical condition deteriorated. He was eventually diagnosed with pylephlebitis with associated inferior mesenteric vein thrombosis. He was successfully treated with IV antibiotics and warfarin. Pylephlebitis should not be overlooked as a differential in an appropriate clinic setting as it has a high mortality rate.